Production of Vitamin D(3) Enriched Biomass of Saccharomyces Cerevisiae as A Potential Food Supplement: Evaluation and Optimization of Culture Conditions Using Plackett–Burman and Response Surface Methodological Approaches - Mohajeri Amiri, Morteza (Iran J Pharm Res, 2019)
Vitamin D deficiency causes osteoporosis, osteopenia, fractures, rickets, and more recently is linked with some chronic illnesses such as cancer. Because of the safety and probiotic properties of the yeast Saccharomyces cerevisiae, we hypothesized that yeast cells enriched with cholecalciferol (vitamin D(3)) could represent a solution for prevention or treatment of vitamin D deficiency. In this study S. cerevisiae was used as a vitamin D(3 )accumulator for the first time and the optimal conditions for enrichment of S. cerevisiae were determined. The Plackett-Burman screening studies were used for selection of the most important factors affecting cholecalciferol entrapment. Response surface methodology was employed for optimization of cholecalciferol accumulation in S. cerevisiae cells by using Box-Behnken design. A modified quadratic polynomial model fit the data appropriately. The optimal points of variables to maximize the response were cholecalciferol initial concentration of 358021.16 IU/mL, tryptone concentration of 1.82 g/L, sucrose concentration of 7.13 % (w/v), and shaking speed of 140.46 rpm. The maximum amount of cholecalciferol in dry cell weight of S. cerevisiae was 4428.11 IU/g. The cholecalciferol entrapment in yeast biomass increased about two-folds in optimized condition which indicates efficiency of optimization.